Determinants of successful breastfeeding by young mothers in New Zealand : a thesis presented in partial fulfillment of the requirements for the degree of Masters in Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Polglaze, Rebekah Leigh (Massey University, 2017)
Background: International research has shown that younger mothers are less likely to initiate/maintain breastfeeding (BF) than older women. Optimising BF maintenance in young mothers is important because early cessation of BF has been associated with negative health outcomes for the infant, which may extend beyond infancy into adulthood. Despite this, little is known about the facilitators of successful BF in this group. Therefore, the purpose of this study was to investigate the factors that enabled a group of mothers who gave birth at a young age to successfully breastfeed for at least 4 months. Objective: To gain an in-depth understanding of the factors that led to a successful breastfeeding experience in mothers who gave birth at a young age. Methods: Seventeen positive deviants were identified. These were mothers who gave birth under the age of 25 years, who had successfully BF for at least 4 months. Participants were recruited through various support groups and breastfeeding networks. Semi-structured in-depth interviews were conducted in person or over the phone with each of the seventeen mothers. The interviews were recorded and transcribed, which enabled theme identification. Demographic information was also collected using a short questionnaire. A thematic analysis was used to analyse the qualitative data obtained from each mother’s breastfeeding experiences. Interpretative phenomenology was used to extract themes from the transcripts, these were then double-checked by two researchers in the research team. Results: Participants were located throughout the North Island of New Zealand (NZ). Eleven mothers identified themselves as NZ European, three mothers identified as NZ European and Māori, and one mother identified as NZ European and Hawaiian. The mothers had given birth between the age of 15 through to 24 years and these births occurred between 2004 and 2017. Despite purposive sampling, of mothers who had successfully BF, participants identified core barriers to BF. These barriers were explored in depth before enablers of BF could be identified and examined. The key barriers include lack of breastfeeding knowledge, expectations, which differed from the lived experience, the quality of the initial support for BF, lack of ongoing support for BF and initial difficulties with the practice BF. Once the core barriers to BF had been fully explored, it was possible to identify and examine the enablers of successful BF. It became evident through the data analysis that the mothers found alternative solutions to overcome these barriers. These solutions were categorised into three key enablers, resilience in the face of adversity, a positive breastfeeding culture and the economy of BF. These factors facilitated the mothers to overcome the barriers they were faced with, which enabled them to successfully breastfeed. Conclusion: Intrinsic motivation amongst positive deviants appears to be a driver of information and support seeking behaviour, which enhances self-efficacy and breastfeeding resilience amongst young mothers.
Keywords: Breastfeeding; Teenage mothers; Young mothers; New Zealand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Domestic science and nutrition